Penerapan Total Quality Management (TQM) dalam Menjaga Kualitas Bibit Tanaman dan Buah di Persada Farm Bogor - Ananda, Muhammad Rizky; Decency, Hanina Anggisya; Azhari, Anisa Nur; Faisal, Faisal; Praja, Muhammad Dzikra Asqalani H S Chandra; Apriliani, Fany (Penerbit Widina, Widina Media Utama, 2025)
This community service program aimed to analyze and assist in the implementation of Total Quality Management (TQM) to maintain the quality of plant seeds and fruits at Persada Farm, Bogor. Using the Participatory Action Research (PAR) approach, the program was carried out through stages of quality issue identification, development of Standard Operating Procedures (SOP) based on TQM principles, technical training, as well as continuous monitoring and evaluation. Data were collected through structured interviews, field observations, and document analysis, supported by Pareto and fishbone diagrams to identify root causes of quality issues. The results indicate that management involvement, customer focus, standardized quality control, and employee recognition have been effectively implemented to support quality consistency. Nevertheless, key challenges remain, including limited regular training and the need to balance production targets with quality maintenance. This program has had a positive impact on improving human resource capacity, fostering a quality-oriented work culture, and serving as a replicable model for TQM implementation in other horticultural sectors.ABSTRAKKegiatan pengabdian ini bertujuan untuk menganalisis dan mendampingi penerapan Total Quality Management (TQM) dalam menjaga kualitas bibit tanaman dan buah di Persada Farm Bogor. Menggunakan pendekatan Participatory Action Research (PAR), program dilaksanakan melalui tahapan identifikasi masalah mutu, penyusunan SOP berbasis prinsip TQM, pelatihan teknis, serta monitoring dan evaluasi berkelanjutan. Data diperoleh melalui wawancara terstruktur, observasi lapangan, dan analisis dokumen, dengan bantuan diagram Pareto dan fishbone untuk mengidentifikasi akar permasalahan. Hasil pelaksanaan menunjukkan bahwa prinsip keterlibatan manajemen, fokus pada pelanggan, kontrol mutu terstandar, dan apresiasi karyawan telah berjalan efektif dalam mendukung konsistensi mutu. Meskipun demikian, tantangan utama yang dihadapi adalah keterbatasan pelatihan berkala dan kebutuhan menyeimbangkan target produksi dengan pemeliharaan mutu. Program ini memberikan dampak positif terhadap peningkatan kapasitas sumber daya manusia, budaya kerja berorientasi mutu, serta menjadi model penerapan TQM yang berpotensi direplikasi pada sektor hortikultura lainnya.